2018
DOI: 10.1021/acsomega.8b03178
|View full text |Cite
|
Sign up to set email alerts
|

Starlike Branched Polyacrylamides by RAFT Polymerization—Part I: Synthesis and Characterization

Abstract: Starlike branched polyacrylamides (SB-PAMs) were synthesized using reversible addition–fragmentation chain transfer copolymerization of acrylamide (AM) and N,N′-methylenebis(acrylamide) (BisAM) in the presence of 3-(((benzylthio) carbonothioyl)thio)propanoic acid as a chain transfer agent, followed by chain extension with AM. The amount of incorporated BisAM in the core and the amount of AM during chain extension have been systematically varied. Core structures were achieved by incorporation of total monomer r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 55 publications
(155 reference statements)
0
11
0
Order By: Relevance
“…The branched polymer was designed for maximum branching and a balance of water solubility according to a procedure in the literature. 16 We believe that the higher the branching degree, the higher the heavy oil viscosity reduction efficiency. The average molecular weight (M n ) of the SB polymer is determined by GPC analysis between 5.5 and 22 × 10 4 g/mol and polydispersity index (PDI) between 1.57 and 6.95 (Table 1).…”
Section: Acsmentioning
confidence: 98%
“…The branched polymer was designed for maximum branching and a balance of water solubility according to a procedure in the literature. 16 We believe that the higher the branching degree, the higher the heavy oil viscosity reduction efficiency. The average molecular weight (M n ) of the SB polymer is determined by GPC analysis between 5.5 and 22 × 10 4 g/mol and polydispersity index (PDI) between 1.57 and 6.95 (Table 1).…”
Section: Acsmentioning
confidence: 98%
“…[30,50] Another non-standard approach can be based on playing with polymer architecture (hyperbranched vs linear), to tune the viscoelastic properties. [51,52] Particularly interesting is also the use of thermoviscosifying polymers for high-temperature reservoirs. [30,[53][54][55] This approach introduces the use of "smart" polymers, able to display the desired properties (in this case an increase in viscosity), only when and where required, at the high temperature of the reservoir.…”
Section: Polymer Floodingmentioning
confidence: 99%
“…Hence, facile, highly efficient, and cost-effective preparation of branched PAMs with a specific structure and unique properties has become a hot topic and has attracted intensive research interest. 10,22 Generally, the grafting-from strategy is an efficient route for the preparation of branched polymers. 23 It has been demonstrated that PAM polymers with precise chemical composition, well-defined molar mass, and complex structure were successfully synthesized using the grafting-from approach combined with reversible-deactivation radical polymerization methods, such as atom transfer radical polymerization (ATRP) and reversible addition−fragmentation chain transfer (RAFT) polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the aforementioned discussion, the distinctive rheology characteristics endow the branched PAMs with wide potential applications in various fields. Hence, facile, highly efficient, and cost-effective preparation of branched PAMs with a specific structure and unique properties has become a hot topic and has attracted intensive research interest. , …”
Section: Introductionmentioning
confidence: 99%